OPEN FLAP DEBRIDEMENT TREATMENT WITH BOVINE-DERIVED XENOGRAFT IN CHRONIC PERIODONTITIS : A CASE REPORT - Pritia, Mardha Ade; Karina, Vincensia Maria (Odonto : Dental Journal, 2024)
Backgrounds: Chronic periodontitis is a periodontal tissue disease caused by specific microorganisms, resulting in periodontal tissue destruction. The gold standard for cases of periodontal tissue destruction is regenerative flap surgery combined with bone graft. The aim of this case report is to describe the repair of bone defects caused by chronic periodontitis with open flap debridement treatment combined with bovine-derived xenograft bone graft and pericardium membrane. Case: A 46-year-old female patient came complaining that her right upper back tooth was swollen and hurt while eating. Clinical findings showed that tooth 16 had grade 2 mobility with a 7 mm periodontal pocket on the distal side accompanied by vertical bone loss on radiographic examination.Method: Emergency treatment was carried out for drainage of the abscess on tooth 16, and then antibiotic medication was given. Initial treatment involves scaling and root planing, occlusion adjustment and splinting. Next, open flap debridement was carried out on tooth 16, bone graft application (Ti-OSS®), followed by pericardium membrane application. Discussion: Evaluation of the results was carried out up to 3 months after treatment; it was found that clinical attachment loss (CAL) was reduced, and radiographic images showed an increase in bone in the distal tooth 16.Conclusion: The use of bovine-derived xenograft bone-graft and pericardium membrane is able to increase the regeneration of alveolar tissue and bone in cases of chronic periodontitis.